Determinants of Green Purchase Intentions for Eco-friendly Skincare Products - Royani, Ida; Sofriana Imaningsih, Erna (Journal of Applied Business, Taxation and Economics Research, 2024)
Rising public awareness of various environmental issues has significantly altered consumer behavior, leading to a greater preference for eco-friendly products. This study aims to examine and evaluate the impact of environmental concern, altruistic values orientation, and perceived behavioral control on green purchase intention, with attitude as a mediating variable. The subjects of this research are individuals aware of environmental issues and the N’PURE skincare product line, residing in Jakarta, Bandung, Semarang, Surabaya, Yogyakarta, and Tangerang. A total of 153 respondents participated in this study. Purposive sampling was employed for sample selection, and the analysis was conducted using structural equation modeling (SEM) with the SmartPLS analytical tool. The study findings reveal that environmental concern, altruistic value orientation, and perceived behavioral control play significant and substantial roles in shaping consumer attitude. Both environmental concern and altruistic value orientation contribute positively, albeit modestly, to the intention to purchase eco-friendly products. Conversely, perceived behavioral control demonstrates a strong and significant effect in determining consumers' intentions to buy green products. Additionally, attitude significantly influences the propensity of consumers to purchase eco-friendly products. Consumer attitude fully mediates the impact of environmental concern on the intention to choose green products, as well as the effect of altruistic value orientation on this intention. Meanwhile, attitude serves as a partial mediator in the influence of perceived behavioral control on the intention to buy eco-friendly products. This study provides valuable theoretical and practical insights into consumer purchasing patterns regarding eco-friendly products.